(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Massive Open Online Courses (MOOCs) is the recent changing agent of teaching and learning environment in this digital era. With the recent development in the LIS field, different library and Information Science courses are also offered in MOOCs platform. SWAYAM i.e Study Webs Active Learning for Young Aspiring Minds is a programme of Ministry of Human Resource Development (MHRD) and All India Council for Technical Education (AICTE), Government of India to provide an integral teaching learning platform in online mode to the academicians. In this study it is tried to present a brief discussions on MOOCs, LIS courses offered by MOOCs specially SWAYAM and Challenges faced by Library Professionals in facilitating MOOCs.